2016
DOI: 10.1186/s13030-016-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to the mental health of women who were pregnant at the time of the Great East Japan earthquake: analysis from month 10 to month 48 after the earthquake

Abstract: BackgroundThe Great East Japan Earthquake occurred at 2:46 p.m. on March 11, 2011. The epicenter was off the coast of Miyagi prefecture, and the magnitude of the earthquake was 9.0 with a maximum seismic intensity of 7.0. Although it has already been four years, victims continue to have complex problems. In the stricken areas of Miyagi prefecture, almost ten percent of the residents continue to live in temporary housing. Life altering events that force relocation and a change of living environment are known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Pregnant women and newborns are vulnerable in times of disaster, and recent large‐scale disasters in various locations worldwide have had a major impact on these patient groups 4–9 . Several studies have reported higher rates of preterm births and low‐birth‐weight infants during large‐scale disasters 10–12 .…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women and newborns are vulnerable in times of disaster, and recent large‐scale disasters in various locations worldwide have had a major impact on these patient groups 4–9 . Several studies have reported higher rates of preterm births and low‐birth‐weight infants during large‐scale disasters 10–12 .…”
Section: Discussionmentioning
confidence: 99%
“…Well-known factors frequently associated with postpartum depression in a normal setting, both in Japan and overseas, include obstetrical history 22 , 38 (eg, maternal age, 28 , 31 first delivery, miscarriage and stillbirth, 15 cesarean section, and presence of congenital anomalies in the child), as well as economic status, 27 , 32 , 34 , 38 , 39 partner support, 30 , 33 , 40 family relationships, 38 lack of childcare support, 27 negative feelings toward pregnancy, 25 and a lack of maternal affection toward their child. 25 , 38 Miscarriage and stillbirth were shown to be associated with depressive symptoms both in the primary survey for FY 2011, 15 and in the 8-year period FY 2011–2018.…”
Section: Discussionmentioning
confidence: 99%
“…The health of women, especially pregnant women, has been investigated in the areas affected by the Great East Japan Earthquake [22][23][24]; however, no research has been conducted with regard to cancer screening. In the present study, we first clarified the difference in the CCS-R of the Miyagi Prefecture before and after the Great East Japan Earthquake.…”
Section: Discussionmentioning
confidence: 99%